Pengaruh DPS, EPS dan ROE Terhadap Harga Saham Syariah - Irton Irton (Jurnal Ilmiah Ekonomi Islam, 2020)
This objective of the study is to investigate effect of dividend per share (DPS) , earning per share (EPS), and return on equity (ROE) to syariah stock price in Indonesian Stock Exchange. The Hypothesis are tested applying single regression model, which stock price are regressed with dividend per share, earning per share, and return on equity. Stock price are independend variable and dividend per share, earning per share, and return on equity as a dependen variable. Stock price are measure using the valuation model, which average price from beginning and ending years for observation 2016-2018. The study uses the samples 109 syariah stock listed on the Indonesian Stock Exchange for observation period of 2016-2018. The classical test are developed to test Autocorellation test, multicollinearity test. The t-test and F-test used to hypothesis test. The result of this study supported the proposed hypothesis that show that hypothesis 1,2, are received and hypothesis 3 are rejected. This study show that dividend per share, earning per share, and return on equity have effect to syariah stock prices.